Simulation of alkali-silica reaction model in a concrete gravity dam at the macroscale and mesoscale - Itam Z.; Beddu S.; Mohammad D.; Kamal N.L.M.; Razak N.A.; Hamid Z.A.A. (Elsevier Ltd, 2023)
Computer software; Concretes; Continuum damage mechanics; Silica; Stochastic systems; Alkali contents; Alkali-silica reaction; Concrete; Concrete gravity dams; Macroscales; Meso scale; Reaction modelling; Relative porosity; Relative temperatures; Silica content; Deformation